Analisis Putusan Pengadilan yang Merampas untuk Negara Barang Bukti Kendaraan Bermotor dalam Tindak Pidana Narkotika (Studi Putusan Nomor: 99/Pid.Sus/2024/PN.Liw.) - Febri Anggraini; Ahmad Irzal Fardiansyah; Rinaldy Amrullah (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study analyzes a court decision that confiscated a motor vehicle used in a narcotics crime for the state, as regulated in Article 101 of Law No. 35 of 2009 on Narcotics. The main problem lies in determining the criminal liability of the perpetrator and assessing whether the confiscation of the vehicle meets the principle of legal certainty, especially when the ownership of the vehicle is unclear and may belong to a third party. This research employs a normative juridical approach, combining statutory and conceptual analyses based on secondary legal materials. The findings show that the perpetrator’s criminal liability was established through the fulfillment of legal capacity, intent (mens rea), and absence of justifying or excusing reasons. However, the court’s decision to confiscate the vehicle failed to ensure legal certainty because ownership was not clearly verified in the trial process. This study contributes to the discourse on the protection of third-party property rights and emphasizes the need for judicial consistency in applying the principle of legal certainty in narcotics-related confiscation cases.